Mortality in pulmonary arterial hypertension due to congenital heart disease: Serial changes improve prognostication. (15th September 2017) - Schuijt, M.T.U.; Blok, I.M.; Zwinderman, A.H.; van Riel, A.C.M.J.; Schuuring, M.J.; de Winter, R.J.; Duijnhouwer, A.L.; van Dijk, A.P.J.; Mulder, B.J.M.; Bouma, B.J.
Abstract: Background: Adult patients with pulmonary arterial hypertension due to congenital heart disease (PAH-CHD) suffer from high mortality. This underlines the importance of adequate risk stratification to guide treatment decisions. Several baseline parameters are associated with mortality, however, their prognostic value may weaken after years of follow-up. Therefore we investigated the prognostic value of serial changes in standard clinical parameters in PAH-CHD. Methods: In this prospective observational cohort study we included consecutive PAH-CHD adults, between 2005 and 2016. Control visits to the outpatient clinic were standardized, including functional, biochemical and echocardiographic tests, according to the guidelines. The prognostic value of serial changes was determined with time-dependent Cox regression. Results: Ninety-two patients with PAH-CHD were included (age 43 ± 15 years, 34% male, 38% Down, 73% Eisenmenger). During a median follow-up of 6.0 (IQR 3.7-9.3) years, 35 (38%) patients died. Serial changes in World Health Organization functional classification (WHO-FC, HR 18.34 for onset class IV), six-minute walk distance (6-MWD, HR 0.65 per 50 m), oxygen saturation at peak exercise (peak SaO2, HR 0.74 per 5%), NTproBNP (HR 2.25 per 1000 ng/l) and echocardiographic right ventricular function (TAPSE, HR 0.80 per 0.5 cm) significantly predicted mortality. Moreover, serial changes in these parameters were more potent predictors compared to baseline parameters, based on reduction in − 2 log likelihood. Conclusions: Serial changes in standard clinical parameters have more prognostic value compared to baseline parameters in PAH-CHD. Our results emphasize the importance of screening for serial changes since periodical assessment could guide treatment decisions to delay disease progression.